The 2D resistivity imaging method in mountainous area over different slope - Aziz, Bakhtiar Qader (Sulaimani Journal for Pure and Applied Sciences, 2013)
Assessing the reliability of the 2D electrical resistivity imaging method is investigated in mountainous areas. Several profiles are surveyed on different surface slopes ranging between 17° to 55° degrees. Two types of electrode arrays with different electrode spacing (2.0, 3.0 and 5.0 meters) are used. Repeated measurements are carried out for each profile by using different field parameters such as data density, pulse duration and voltage. The inverse sections are compared with the drilled bore holes in the area. The results show that the 2D resistivity imaging works well in the mountainous area when suitable field parameters are selected. The study has proved that the inverse sections are highly sensitive to the number of data points. The optimal number of data points has direct relation with surface slope, number of electrodes and electrode spread. On the other hand pulse durations and voltages magnitude have no significant effects on the quality of the field data. An empirical equation is suggested for the optimal acceptable number of data points that has a direct relation to the profile length, number of electrodes, electrode spacing and angle of the slope.